From Representation to Cartelization: The Role of Political Parties in Indonesia - Alfan Huda; Abdul Rachman Sopyan; Ali Maksum; Dzulkarnain Jamil (Indonesian Journal of Political Studies, 2026)
The presence of political parties is essential for channelling the people’s aspirations, and the cartel of political parties shows the weakening of democracy. Therefore, research on the cartelization of political parties in Indonesia is essential to determine why parties create political cartels. This study describes and analyzes the causes of political party cartelization in local election. This research collected qualitative data gathered collaboratively using structured interviews. Purposeful sampling was used to select the informants. The data analysis procedures employed interactive models and involved data collection, data reduction, data display, conclusion drawing, and validating the data utilizing triangulation stages. Findings suggested that the cartelization of political parties perpetuated the dynastic politics. Moreover, the presence of a political cartel indicates the existence of oligarchy power. Being restrained by the oligarchy power, political parties failed to give better alternatives for leadership reform and allowed leadership to be held by incumbent families.